Medical dura mater (spinal mater) repair hydrogel and kit
By using hydrogels formed by chitooligosaccharides with polyethylene glycol succinimide active ester, the problems of high swelling rate and lack of anti-bleeding and infection activity in existing products are solved, and low swelling rate, slow degradation and antibacteriality are achieved. The effect of stopping bleeding reduces product costs.
Patent Information
- Application Number
- CN202411565412.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing dura repair medical hydrogel products have high swelling rate, are prone to compress nerves, and lack the activity to prevent bleeding and infection, which is costly.
Using chitooligosaccharide as the nucleophilic component to form a hydrogel with the two-arm/four-arm polyethylene glycol succinimide active ester. By adjusting the pH value and concentration of the components, the cross-linking degree of the hydrogel is controlled and Degradation time.
It reduces the swelling rate of the hydrogel, reduces the risk of compression on the central nervous system, improves the degradation time and biocompatibility of the hydrogel, has the effect of preventing bleeding and anti-infection, and reduces product costs.
Smart Images

Figure CN119424750A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical degradable artificial synthetic hydrogel adhesives, in particular to a medical dura mater (spinal) membrane repair hydrogel and a kit. Background Art
[0002] Dura sealant is a medical material used to repair dura defects, mainly used in neurosurgery and spinal surgery, especially when the dura is cut or damaged. It prevents postoperative cerebrospinal fluid (CSF) leakage and significantly reduces postoperative complications such as CSF leak and pseudomeningocele.
[0003] Dura mater sealant is usually composed of polyethylene glycol (PEG) and other polyamino compounds. These materials can form a stable hydrogel network at the surgical site. Dura mater sealant has the function of rapid molding and preventing cerebrospinal fluid leakage. This makes dura mater sealant an important tool in neurosurgery, effectively improving the success rate of surgery and the quality of postoperative recovery of patients.
[0004] In 2004, DuraSeal Dural Sealant was first launched in the US FDA (PMA No.: P040034b); the product is mainly composed of two components, including the electrophilic component: four-arm polyethylene glycol succinimidyl glutarate (4-ARM-PEG-SG):
[0005]
[0006] And the nucleophilic component: three lysine:
[0007]
[0008] composition.
[0009] From the perspective of chemical reaction principles, these two components can undergo the following chemical reactions at room temperature:
[0010]
[0011] The succinimide group (SG group) in 4-ARM-PEG-SG can react rapidly with the primary amino group of trilysine in aqueous solution at room temperature to form a mutually covalently cross-linked hydrogel. In clinical use, in addition to reacting with trilysine to form a hydrogel, the 4-ARM-PEG-SG in this product can also undergo a covalent cross-linking reaction with the free amino groups of collagen (the main component of the dura mater) in the patient's dura mater. The free amino groups in the collagen form a covalent cross-linking reaction with 4-ARM-PEG-SG, so that stable covalent cross-links are formed between the hydrogel and the patient's dura mater, completely sealing the defects in the dura mater and achieving its clinical purpose.
[0012] The medical hydrogel products for repairing dura mater (spinal cord) that are currently in clinical use include the following products, see Table 1.
[0013] Table 1 Summary of dura mater medical adhesive products
[0014]
[0015] From the composition of the above products, it can be seen that the products are all based on the chemical reaction between the active ester group of succinimide and the free amino group, that is, they all follow the same chemical reaction mechanism, the difference is the selection of different nucleophilic reagents. The nucleophilic reagents used in the products that have been verified mainly include: trilysine, polyethyleneimine, and polylysine. Among these three, the primary amino groups of trilysine and polyethyleneimine have higher chemical reactivity with 4-ARM-PEG-SG.
[0016] But the molecular formula of polylysine is as follows:
[0017]
[0018] Although there is an amino group in the molecule, since the amino group is not a primary amino group, its nucleophilicity is reduced, so that the reaction activity of the molecule with 4-ARM-PEG-SG is low, making the reaction difficult to occur.
[0019] Shandong Saikesaisi Biotechnology Co., Ltd. developed Sainaoning absorbable dura mater sealing medical glue, CN201610168941.5 biodegradable medical hydrogel and its preparation method and application, the patent provides a nucleophilic component composed of trilysine and polyethyleneimine (molecular weight 1800, primary amino molar content of 35%). The electrophilic component composed of four-arm N-hydroxysuccinimide propionate ( / succinate / glutarate / sebacate, etc.)-based polyethylene glycol with a molecular weight of 10,000 is used, and the above two components are used to form a hydrogel.
[0020] Shenzhen Maipu Regenerative Medicine Technology Co., Ltd. developed a dura mater medical glue, CN201610286118.4 medical hydrogel composition, medical hydrogel and its preparation method and application. The invention relates to a medical hydrogel composition, which includes: a nucleophilic component and an electrophilic component. The nucleophilic component uses polylysine and polyethyleneimine; the electrophilic component includes one or more of four-arm-polyethylene glycol-succinimidyl glutarate, four-arm-polyethylene glycol-succinimidyl succinate, and four-arm-polyethylene glycol-succinimidyl carbonate.
[0021] Beijing Nuokangda Pharmaceutical Technology Co., Ltd. invention patent, CN201910720247.3 A method for preparing an anti-adhesion gel precursor, an anti-adhesion gel and a kit. The invention includes three components. Including a first component with electrophilic properties: four-arm-polyethylene glycol-succinimidyl glutarate, four-arm-polyethylene glycol-succinimidyl succinate, four-arm-polyethylene glycol-succinimidyl carbonate, four-arm-polyethylene glycol-succinyl ester, eight-arm-polyethylene glycol maleimide ester, eight-arm-polyethylene glycol maleimide ether, eight-arm-polyethylene glycol succinyl ester, eight-arm-polyethylene glycol succinyl dimethyl ester, eight-arm polyethylene glycol succinyl succinate, eight-arm-polyethylene glycol succinimidyl succinamide, eight-arm polyethylene glycol succinyl glutarate, eight-arm polyethylene glycol succinyl pentamethylenediamine at least one. The second component is a polypeptide compound, and the polypeptide compound is selected from trilysine or its derivatives. The third component is a compound put into the second component, which mainly plays an antibacterial role, and is preferably carboxymethyl chitosan.
[0022] Beijing Nuokangda Pharmaceutical Technology Co., Ltd. invention patent, CN202110351993.7 In situ drug-loaded hydrogel and its preparation method and application, provides an in situ drug-loaded hydrogel and its preparation method and application. The in situ drug-loaded hydrogel of the invention can be used for tissue wound sealing, repair, filling or treatment. The electrophilic reagent is a multi-arm polyethylene glycol derivative, and the derivative selected is four-arm polyethylene glycol succinimidyl succinate, four-arm polyethylene glycol succinimidyl glutarate, eight-arm-polyethylene glycol-succinimidyl glutarate, or eight-arm-polyethylene glycol-succinimidyl glutarate. The nucleophilic reagent uses a terminal amino group compound, including at least one or a combination of several selected from polylysine, polylysine salts, carboxymethyl chitosan, and chitosan.
[0023] Beijing Nokanda Pharmaceutical Technology Co., Ltd. Invention patent: Application No. 202110837273.1 "Peripheral nerve composite catheter and its preparation method and application". A peripheral nerve composite catheter was prepared. Its hydrogel column is made by the reaction of multi-arm polyethylene glycol succinimidyl glutarate and trilysine salt. Its active nucleophile is trilysine salt.
[0024] Invention patent of Wuhan University Dai Honglian et al., CN202311751366.8 A platelet-rich plasma hydrogel with slow release of growth factors and its preparation method and application. The platelet-rich plasma hydrogel has a double network structure consisting of a first network and a second network interpenetrating each other, wherein the first network is obtained by cross-linking multi-arm polyethylene glycol active ester with platelet-rich plasma, and the second network is obtained by cross-linking photo-induced methacrylylated polymer. The electrophilic reagent in this patent is a multi-arm polyethylene glycol active ester, and platelet-rich plasma is used as a nucleophilic reagent to cross-link with the electrophilic reagent to form a hydrogel.
[0025] The products of the prior art have the following technical problems:
[0026] (1) The products currently in clinical use have a high swelling rate and are prone to compressing nerves. The swelling rate refers to taking out the hydrogel after soaking it in neutral saline for a period of time, recording the initial hydrogel weight (W1) and the final hydrogel weight (W2), and the swelling rate S (%) = W2 / W1×100%. The swelling rate reflects the degree of internal cross-linking of the hydrogel. Generally, the lower the degree of cross-linking, the higher the swelling rate. Hydrogels with high swelling rates have lower degrees of cross-linking, so their in vivo and in vitro degradation times are faster. For existing products on the market, the published swelling rate and degradation performance data are shown in Table 2.
[0027] Table 2 Swelling rate and degradation performance of existing marketed products
[0028]
[0029] Dura mater medical glue is expected to be used for the repair of human dura mater or dura mater. Dura mater is a thin connective tissue membrane that wraps the central nervous system, including the brain and spinal cord. After the medical glue is implanted in the human body, the gel swells, compressing the nerves, causing headaches and dizziness, and even causing life-threatening conditions in severe cases. Therefore, the lower the swelling rate of the medical glue, the better. However, the swelling rate of the products currently on the market is generally high, and the swelling rate is usually only required to be less than 200%. Therefore, the products currently used clinically still have a certain risk of swelling and compressing the central nervous system.
[0030] (2) Existing products only have a physical sealing effect and have no biological activity.
[0031] Clinically, bleeding and infection remain the main adverse reactions of dura mater repair.
[0032] According to the FDA registration information of DuraSeal dura sealant (P040034b), the surgical site infection rate in clinical trials was 8.1% (9 / 111) and the bleeding rate was 3.6% (4 / 111). Postoperative infection and bleeding are key factors affecting its clinical use effect.
[0033] At present, the medical adhesives for dura mater (spinal membrane) used clinically at home and abroad have no activity to prevent bleeding and infection. Therefore, it is of great clinical significance to develop medical adhesives for repairing dura mater (spinal membrane) with antibacterial and anti-bleeding abilities.
[0034] (3) The cost of existing products is high. The dura mater medical glue currently used mainly uses polyethylene glycol active ester and trilysine as the main components. Both materials can only be synthesized artificially and are expensive, which pushes up the manufacturing cost of such products and increases the burden on patients. Summary of the invention
[0035] In view of the problems existing in the prior art, the present invention provides a medical dura mater (spinal) repair hydrogel and a kit. The hydrogel is made of chitosan oligosaccharide as a nucleophilic component. On the one hand, its swelling rate is within 120%, which can effectively reduce the risk of compressing the central nervous system and reduce clinical complications; on the other hand, based on the hemostatic and antibacterial effects of chitosan oligosaccharide, the absorbable dura mater (spinal) repair medical glue has the effects of preventing intraoperative and postoperative bleeding and resisting infection.
[0036] The technical solution adopted by the present invention is a medical dura mater (spinal cord) repair hydrogel, which includes a first component and a second component, wherein the first component is chitosan oligosaccharide; the second component is two-arm / four-arm polyethylene glycol succinimide active ester; the first component is dissolved in a weakly alkaline buffer solution, and the second component is dissolved in a weakly acidic buffer solution, and the two-component solutions are mixed and reacted to form a hydrogel, and the molar concentration ratio of the free amino groups of the chitosan oligosaccharide in the hydrogel to the succinimide ester in the two-arm / four-arm polyethylene glycol succinimide active ester is 1.0 to 1.5:1.
[0037] The two-arm / four-arm polyethylene glycol succinimide active ester is one or more of two-arm / four-arm polyethylene glycol succinimide glutarate, two-arm / four-arm polyethylene glycol succinimide succinate, and two-arm / four-arm polyethylene glycol succinimide sebacic acid ester.
[0038] The molecular weight of the chitosan oligosaccharide is 340-2000Da, and all chitosan oligosaccharides are deacetylated chitosan oligosaccharides with 2 or more free amino groups.
[0039] The molecular weight of the two-arm / four-arm polyethylene glycol succinimide active ester ranges from 2000 to 40000 Da.
[0040] The weak alkaline buffer is a sodium tetraborate buffer with a pH value between 7.5 and 10.0; the weak acidic buffer is a phosphate buffer with a pH value between 4.0 and 6.5.
[0041] After the hydrogel is soaked in physiological saline, the pH value of the soaking solution is 6.0-9.0.
[0042] The color developing agent Brilliant Blue 85 is added to the second component to make the hydrogel appear blue, so that the surgeon can visually observe the specific location where the hydrogel is sprayed during the operation.
[0043] The first component is dissolved in a weak alkaline buffer, and the concentration of chitosan oligosaccharide is 10-50 mg / mL; the second component is dissolved in a weak acidic buffer, and the concentration range of two-arm / four-arm polyethylene glycol succinimide active ester is 80-800 mg / mL.
[0044] The first component and the second component are stored separately, and the two components are mixed by a drug mixing device before use, wherein the second component two-arm / four-arm polyethylene glycol succinimide active ester is stored separately in a freeze-dried state.
[0045] A kit containing the medical dura mater (spinal) membrane repair hydrogel.
[0046] The advantages and technical effects of the present invention are as follows:
[0047] 1. The swelling rate of the hydrogel prepared by the present invention is less than 120%. Due to the low swelling rate, it will not cause product swelling and compression of nerve tissue after implantation, thus avoiding complications related to nerve compression and nerve damage caused by swelling of the hydrogel.
[0048] 2. The in vivo degradation time of the hydrogel prepared by the present invention is 6-24 weeks, which is milder than the existing clinical products (4-8 weeks). After the hydrogel is implanted in the human body, it can slowly complete the degradation of the hydrogel and the reconstruction of the dura mater tissue along with the soft tissue repair process, so that the hydrogel will not disintegrate and degrade due to its own instability after being implanted in the human body at 37°C. The chemical composition and ratio of the hydrogel are more suitable for the repair of dura mater defects in neurosurgery.
[0049] 3. The present invention adopts chitosan oligosaccharide as the nucleophilic component, which is a natural polysaccharide extracted from nature or its derivatives, and is not an artificially synthesized chemical substance. The cost is relatively low, the product price is low, and the burden on patients can be reduced.
[0050] 4. After the dura mater defect in neurosurgery is usually sealed with medical glue, postoperative bleeding and infection are still important problems that cause complications for patients. Conventional dura mater medical glue does not have the function of preventing bleeding and infection, which often causes bleeding or infection complications after surgery, seriously affecting the healing of patients. The present invention itself has the effects of promoting blood coagulation and anti-infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 It is the thromboelastogram test curve of the coagulation time of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0053] The medical dura mater repair hydrogel of the present invention comprises a first component and a second component, wherein the first component is chitosan oligosaccharide; the second component is two-arm / four-arm polyethylene glycol succinimide active ester; the first component is dissolved in a weakly alkaline buffer solution, and the second component is dissolved in a weakly acidic buffer solution. The two-component solution is mixed and reacted to form a hydrogel, wherein the molar concentration ratio of chitosan oligosaccharide to two-arm / four-arm polyethylene glycol succinimide active ester in the hydrogel is 1.0 to 1.5:1.
[0054] Furthermore, the two-arm / four-arm polyethylene glycol succinimide active ester is one or more of two-arm / four-arm polyethylene glycol succinimide glutarate, two-arm / four-arm polyethylene glycol succinimide succinate, and two-arm / four-arm polyethylene glycol succinimide sebacic acid ester.
[0055] Furthermore, the molecular weight of the chitosan oligosaccharide is 340-2000Da, and the chitosan oligosaccharide is deacetylated chitosan oligosaccharide with 2 or more free amino groups.
[0056] Furthermore, the molecular weight of the two-arm / four-arm polyethylene glycol succinimide active ester ranges from 2000 to 40000 Da.
[0057] Furthermore, the weak alkaline buffer is a sodium tetraborate buffer with a pH value between 7.5 and 10.0; the weak acidic buffer is a phosphate buffer with a pH value between 4.0 and 6.5.
[0058] Furthermore, after the hydrogel is immersed in physiological saline, the pH value of the immersion solution is 6.0 to 9.0.
[0059] Furthermore, the color developing agent Brilliant Blue 85 is added to the second component to make the hydrogel appear blue, so that the surgeon can visually observe the specific location where the hydrogel is sprayed during the operation.
[0060] Furthermore, the first component is dissolved in a weakly alkaline buffer, and the concentration of chitosan oligosaccharide is 10-50 mg / mL; the second component is dissolved in a weakly acidic buffer, and the concentration range of two-arm / four-arm polyethylene glycol succinimide active ester is 80-800 mg / mL.
[0061] Furthermore, the first component and the second component are stored separately, and the two components are mixed by a drug mixing device before use, wherein the second component two-arm / four-arm polyethylene glycol succinimide active ester is stored separately in a freeze-dried state.
[0062] A kit containing the medical dura mater (spinal) membrane repair hydrogel.
[0063] The first component of the present invention adopts chitosan oligosaccharide. The molecular weight of the chitosan oligosaccharide is in the range of 340-2000Da. All chitosan oligosaccharides are deacetylated chitosan oligosaccharides. The nucleophilic reagent of the present invention adopts chitosan oligosaccharide as the main raw material, which is used to replace trilysine, PEI and lysine, and as a nucleophilic reagent, forms a covalent cross-linking reaction with two-arm / four-arm polyethylene glycol succinimide active ester to form a hydrogel. The use of chitosan oligosaccharide as a nucleophilic reagent for dura mater (spinal) medical glue has the following advantages, including: (1) Antibacterial property: chitosan oligosaccharide has natural antibacterial properties and can reduce the risk of infection. (2) Biocompatibility: chitosan oligosaccharide has good compatibility with human tissues and will not cause immune rejection reactions. (3) Degradable: chitosan oligosaccharide can be naturally degraded in the body, and the final product is harmless. (4) Cheap and easy to obtain: chitosan oligosaccharide has the characteristics of low price and good biological activity. (5) Promote tissue regeneration: chitosan oligosaccharide can promote cell proliferation and differentiation, and help repair and regenerate tissues.
[0064] Based on the primary amino repeating units in chitosan oligosaccharides, they show positive charge under physiological conditions, which gives the material dual biological activities of hemostasis and antibacterial. In the early stage of implantation, the positive charge exposed by chitosan oligosaccharides can assist the hemostasis process and promote the formation of blood clots, which can reduce bleeding on the one hand, and establish the coagulation stage in the four stages of tissue regeneration and repair: coagulation, inflammation, proliferation and reconstruction on the other hand, and assist the smooth progress of tissue repair process.
[0065] The present invention adopts chitosan oligosaccharide to replace trilysine, on the one hand, to replace trilysine; on the other hand, by using chitosan oligosaccharide, since it contains more primary amino active groups, the content and molecular weight of polyethylene glycol active ester can be significantly reduced, thereby reducing production costs and reducing the economic burden on patients.
[0066] The nucleophilic component used in the present invention is chitosan oligosaccharide. Chitosan oligosaccharide molecules have repeated free amino groups inside, which can be used as active sites for hydrogel cross-linking reactions. The electrophilic reagent used in the present invention is two-arm / four-arm polyethylene glycol succinimide active ester. The molecular weight range of chitosan oligosaccharide is 340-2000Da.
[0067] In order to control the pH value of the reaction process, chitosan oligosaccharide and two-arm / four-arm polyethylene glycol succinimide are mixed before use to have the most suitable reaction conditions. By adding a buffer to the two main components, chitosan oligosaccharide uses a sodium tetraborate alkaline buffer, and the pH of the solution should be between 7.5 and 10.0 after adding chitosan oligosaccharide; after adding two-arm / four-arm polyethylene glycol succinimide ester to the phosphate buffer, the pH of the solution is between 4.0 and 6.5.
[0068] The two-arm / four-arm polyethylene glycol succinimide active ester has a high reactivity. Since it undergoes a hydrolysis reaction in an aqueous solution, the component needs to be stored in a vial in the form of a lyophilized powder and mixed with a phosphate buffer solution when used to form a second component solution. In addition, in order to enable clinicians to clearly see the spraying site and the state of hydrogel formation during use, Brilliant Blue 85 is added to the lyophilized powder to give the hydrogel a blue color, so that doctors can observe the location and solidification state of the hydrogel formed by the spraying of the two components during clinical use.
[0069] The present invention belongs to a medical absorbable dura mater (spinal) hydrogel adhesive, which is suitable for the repair of dura mater or dura mater defects in neurosurgery. Dura mater and dura mater are connective tissue membranes wrapped around the outer layer of the brain and spinal cord (central nervous system). Clinically, dura mater defects may be caused due to trauma or when craniotomy is required due to intracranial tumors, intracranial hemorrhage, or intracranial hemangioma. If it is not repaired, adverse complications caused by cerebrospinal fluid leakage may occur. Therefore, after the operation is completed, the dura mater defects need to be repaired to maintain the integrity of the dura mater system, keep the cerebrospinal fluid from leaking, and reduce the occurrence of complications. By spraying the absorbable dura mater hydrogel adhesive onto the surface of the defect, a solid hydrogel is formed, the defect is completely closed, the integrity of the dura mater and dura mater can be maintained, cerebrospinal fluid leakage can be prevented, and complications can be reduced, which has important clinical significance.
[0070] When preparing the kit, the first component, chitosan oligosaccharide, is placed in a sodium tetraborate buffer solution with a pH of 7.5 to 10.0, as solution A, and is placed in a syringe marked with A. The phosphate buffer of the matching lyophilized powder is prepared by dissolving sodium dihydrogen phosphate in water for injection. Before using the product, the lyophilized powder needs to be first dissolved in the second component solution and placed in a syringe marked with B. Before use, syringes A and B are mixed with a drug mixing tool to spray out the mixed solution of the two solutions at the same time.
[0071] Example 1
[0072] 1. Preparation of the medical dura mater (spinal) membrane repair hydrogel of the present invention: Taking the preparation of 5 mL of medical dura mater (spinal) membrane hydrogel as an example, the preparation is carried out:
[0073] (1) Solution A: Weigh 64 mg of borax and dissolve it in 2.5 ml of water for injection until it is completely dissolved. Weigh 30 mg of chitosan oligosaccharide with a molecular weight of less than 1000 Da and dissolve it in the borax solution.
[0074] (2) Solution B: Dissolve 156 mg of sodium dihydrogen phosphate dihydrate in 2 mL of water for injection to obtain a buffer solution of solution B. Use 400 mg of lyophilized powder of bi-arm polyethylene glycol succinimidyl glutarate with a molecular weight of 10,000 and 0.5 mg of brilliant blue 85 and dissolve them in solution B.
[0075] (3) Take syringes A and B from the drug mixing device and add solution A and solution B into the solvent accordingly. The volume of both solutions is about 2.5 mL. Put syringes A and B on the drug mixing rack for later use.
[0076] 2. Control group samples
[0077] Control group 1: DuraSeal dura mater medical glue with a nominal volume of 5 ml was selected.
[0078] Control group 2: Shandong Saikesaisi dura mater medical glue with a nominal volume of 5 ml was selected.
[0079] 3. After the gel is configured, perform the test as follows:
[0080] Swelling rate (%) detection: Swelling rate refers to the percentage increase in mass when the hydrogel is saturated in PBS solution after effective cross-linking. The detection method is as follows: the nucleophilic component (first component) and the electrophilic component (second component) are sprayed into a silicone tube with a fixed inner diameter through a two-component mixer to form a cylindrical gel with a diameter of 8 mm and a length of 5 mm in the silicone tube. The cylindrical gel sample is taken out and accurately weighed as W1, and moved to a ground-mouth conical flask, and a pH of 7.4 phosphate buffer preheated to 37±1°C is added. The mass of the test solution is 40% of the test amount. The ground-mouth conical flask is placed in a 37±1°C incubator. After 24 hours, the sample is taken out and the surface moisture is absorbed with filter paper. The weight is weighed and recorded as W2. The gel swelling rate (S, unit %) is calculated according to the following formula. S = (W2-W1) / W1×100%.
[0081] In vitro degradation rate test: Same as the swelling rate test, the gel was extruded into a cylindrical gel with a diameter of φ8mm and a length of 5mm. The solidified gel was taken out and placed in a pH 7.4 phosphate buffer, and then placed in a 60±1℃ constant temperature box. The integrity of the gel was observed every 2 hours. When the gel could not be seen with the naked eye, the in vitro degradation time of the gel was recorded.
[0082] Gel time test: At room temperature (about 20-30°C), use a double mixer to squeeze liquid A and liquid B into a vial, with an extrusion volume of about 0.5-1.0 ml. Start timing immediately after extrusion, then turn the vial over, and stop timing when the gel in the vial solidifies, and record the time t (unit: seconds) required for gelation.
[0083] Coagulation performance: The difference in coagulation reaction time of different samples was tested using a thromboelastograph. Thromboelastogram (TEG) is an indicator that reflects the dynamic changes in blood coagulation (including the formation rate of fibrin, the dissolution state and the firmness and elasticity of the coagulated state). The coagulation reaction time (R) of the thromboelastograph is the period from when the blood sample is placed in the TEG analyzer to when the first fibrin clot is formed. When a procoagulant substance is added to the blood sample, its R value decreases accordingly; when an inhibitory coagulation substance is added to the blood sample, its R value increases accordingly. The specific test method is: take fresh rabbit blood in an anticoagulant tube. Using the whole blood recalcification method, 0.6 ml of 38 g / L sodium citrate anticoagulated blood (blood: anticoagulant = 9:1) was placed in a plastic test tube or a silicon-coated test tube, and the blood sample was mixed with dura mater medical glue at a weight ratio of 3:1. The mixture was incubated at 37°C for 4 hours. Then, whole blood of the three samples was taken, and 0.4 ml of 12.9 g / L CaCl2 solution was added and mixed. The stopwatch was started immediately, and 0.36 ml of the mixed solution was taken into a blood cup for measurement.
[0084] Antibacterial test: Weigh a certain amount of hydrogel (1g) or competitive hydrogel block and place it in a solution with a concentration of (0.8-1.2)×10 3 cfu / ml (denoted as C1) of Staphylococcus aureus liquid, the liquid was placed in a 37℃ constant temperature box for 24 hours, and then the concentration of microorganisms in the liquid was tested again, and the number of bacteria in the liquid was tested C2. Calculate the antibacterial rate % = (C1-C2 / C1) × 100%. When the antibacterial rate result is ≤0, it means there is no antibacterial effect; when the antibacterial rate is between 0-100%, it means there is an antibacterial effect, and the larger the value, the better the antibacterial effect.
[0085] 4. Test results
[0086] The test results are as follows:
[0087]
[0088] Thromboelastography results of clotting time test results are shown in Figure 1 .
[0089] 5. Results Analysis
[0090] According to the results of the thromboelastogram test, the coagulation time of the experimental group was less than that of the control group 1 and the control group 2, indicating that the experimental group had a procoagulant effect. According to the results of the antibacterial test, the antibacterial rate of the experimental group was significantly higher than that of the control group 1 and the control group 2, indicating that the experimental group had antibacterial properties.
[0091] The swelling rate and in vitro degradation test can both reflect the internal crosslinking degree of the hydrogel. The higher the crosslinking degree of the hydrogel, the lower its swelling rate and the longer the corresponding in vitro degradation time. From the perspective of the test group, its swelling rate and in vitro degradation are lower than those of the control group 1 and the control group 2, so from the perspective of the intermolecular crosslinking degree, its crosslinking degree is higher than that of the control group 1 and the control group 2. Although the higher the crosslinking degree, the more conducive it is to reduce the swelling rate and prolong the in vivo degradation and in vitro degradation time, but with the increase of the crosslinking degree, usually its gel time will become shorter and shorter. When the gel time is too short, that is, the gelling speed of the gel is too fast, the two components will be blocked when the double drug mixer is used to mix the drugs due to the excessive gelling and the mixing head, so that the gel cannot be ejected. In this embodiment, the gel time of the test group is less than that of the control group 1 and the control group 2, indicating that the test group shows a faster reaction activity at the beginning of use, and the gelling time of the gel is moderate, and the gelling time can meet clinical needs, and the gelling time will not be too fast to cause the gel to be unable to be ejected. The swelling rate of the test group was lower, indicating that the test group was not prone to local nerve compression caused by swelling after hydrogel implantation during clinical use.
[0092] The proportions in Example 1 of the present invention are only for illustrating the effects of the present invention. The inventor has conducted experiments on various proportions mentioned in the claims, and the effects and principles are the same as those in the embodiments, so they will not be described again.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A medical dura mater repair hydrogel, characterized in that: The method comprises a first component and a second component, wherein the first component is chitosan oligosaccharide; and the second component is a two-arm / four-arm polyethylene glycol succinimide active ester; The first component is dissolved in a weak alkaline buffer, and the second component is dissolved in a weak acidic buffer. The two component solutions are mixed to react to form a hydrogel, and the molar concentration ratio of the free amino groups of chitosan oligosaccharides to the succinimide ester in the two-arm / four-arm polyethylene glycol succinimide active ester in the hydrogel is 1.0 to 1.5:
1.
2. The medical dura mater repair hydrogel according to claim 1, characterized in that: The two-arm / four-arm polyethylene glycol succinimide active ester is one or more of two-arm / four-arm polyethylene glycol succinimide glutarate, two-arm / four-arm polyethylene glycol succinimide succinate, and two-arm / four-arm polyethylene glycol succinimide sebacic acid ester.
3. The medical dura mater repair hydrogel according to claim 1, characterized in that: The molecular weight of the chitosan oligosaccharide is 340-2000Da, and all chitosan oligosaccharides are deacetylated chitosan oligosaccharides with 2 or more free amino groups.
4. The medical dura mater repair hydrogel according to claim 1, characterized in that: The molecular weight of the two-arm / four-arm polyethylene glycol succinimide active ester ranges from 2000 to 40000 Da.
5. The medical dura mater repair hydrogel according to claim 1, characterized in that: The weak alkaline buffer is a sodium tetraborate buffer with a pH value between 7.5 and 10.0; the weak acidic buffer is a phosphate buffer with a pH value between 4.0 and 6.
5.
6. The medical dura mater repair hydrogel according to claim 1, characterized in that: After the hydrogel is soaked in physiological saline, the pH value of the soaking solution is 6.0-9.
0.
7. The medical dura mater repair hydrogel according to claim 1, characterized in that: The color developing agent Brilliant Blue 85 is added to the second component to make the hydrogel appear blue, so that the surgeon can visually observe the specific location where the hydrogel is sprayed during the operation.
8. The medical dura mater repair hydrogel according to claim 1, characterized in that: The first component is dissolved in a weak alkaline buffer, and the concentration of chitosan oligosaccharide is 10-50 mg / mL; the second component is dissolved in a weak acidic buffer, and the concentration range of two-arm / four-arm polyethylene glycol succinimide active ester is 80-800 mg / mL.
9. The medical dura mater repair hydrogel according to any one of claims 1 to 8, characterized in that: The first component and the second component are stored separately, and the two components are mixed by a drug mixing device before use, wherein the second component two-arm / four-arm polyethylene glycol succinimide active ester is stored separately in a freeze-dried state.
10. A kit containing the medical dura mater (spinal) mater repair hydrogel according to any one of claims 1 to 9.
Citation Information
Patent Citations
Biodegradable medicine hydrogel and preparation method and application thereof
CN105778124A
Medical hydrogel compositions, medical hydrogels and their preparation methods and applications
CN105963792B
Anti-adhesion gel precursor, preparation method of anti-adhesion gel, and kit
CN110433344A
In-situ drug-loaded hydrogels, their preparation methods and applications
CN113171463B
Peripheral nerve composite conduit, its preparation method and application
CN113633430B